Literatūrinio modernizmo preliudai XIX–XX amžių sandūros Vilniuje. Interjero kultūra ir privačiojo estetizmo tekstai - Kvietkauskas, Mindaugas (Literatūra, 2015)
The genesis prerequisites of the early literary Modernism appear in Vilnius during the last decade of the 19th century when the city encountered the first manifestations of the cultural consciousness of the modern liberal bourgeoisie. The first publicist texts of the independent Russian media (in 1898 the dailyСеверо-Западное Слово started circulating), and the architectural discourse of the city (the stylistics of Vilnius Land Bank colonies) witness the classical liberal ideology of modernisation according to which the rational progress of civilisation harmoniously coincides with the individualistic values. The then still very scarce texts of Vilnius Russian and Polish literature and aesthetics were gradually moving away from the positivism of the 19th century towards the expression of modern individualism, bourgeois privacy, value liberalism, and aesthetic refinement. Vilnius literary texts generously depicted aesthetical interiors as private individual space, cultural shades from the dehumanising effect of technical progress (W. Benjamin). Aesthetical, closed interior turns into a semantically crucial space in the Vilnius novels Dwór w Haliniszkach (1903) and Z miłości (1903) by the Polish writer E. Jeleńska-Dmochowska. The private interior fantasies and the feeling of social isolation are clear features of mentality in novellas by the Vilnius Russian writer Yevgeny Shveder (Наброски и силуэты, 1904). The larger part of the early creative period of Kazys Puida should also be attributed to the melancholic discourse of the private aestheticism (Iš sermėgiaus krūtinės, 1906, Ruduo, 1906). The texts by the above authors sporadically demonstrated stylistic features of Parnassian and Decadent aestheticisms. The first collection of Polish poems published in the 20th century in Vilnius, the book Fale by Stanisława Szadurska (1906) also represented some melancholic features of the salon aesthetics and the classical French Parnassus. Still this culture of the liberal, cosmopolitan urban modernity and its literary representations in Vilnius, unlike in the centres of Western and Central European literature remained more fragmental and did not create any prominent conflict resistance to further development of the modern literary consciousness. Thus, they should be regarded as a sporadic prologue of such evolution although typologically these texts correspond to the processes in the large European fin-de-siècle cities.